2021
DOI: 10.1002/jgh3.12626
|View full text |Cite
|
Sign up to set email alerts
|

Split‐dose 1 L polyethylene glycol (PEG) with ascorbate is non‐inferior to split‐dose PEG with sodium picosulfate and magnesium citrate with similar tolerability: a randomized study

Abstract: Background and Aim Post‐marketing studies comparing low‐volume polyethylene glycol (PEG)‐based regimens are limited. This randomized study aimed to compare the efficacy and tolerability of a novel 1‐L low‐volume PEG‐based preparation: 1 L PEG+Asc (PEG3350, sodium ascorbate, sodium sulfate, ascorbic acid, sodium chloride, and potassium chloride) with PEG+SPMC (PEG3350, sodium chloride, potassium chloride and sodium sulfate, sodium picosulfate, magnesium oxide, citric acid, and aspartame), prior to routine colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Several studies have reported that 1L PEG is not inferior to 2L PEG or other bowel preparations. [24][25][26] Xin Y et al reported that there were no significant differences in appropriate bowel preparation rates and complication rates in a meta-analysis of randomized, controlled trials with 1L PEG and 2L PEG. [27] Instead of improving compliance and taste, 1L PEG has raised concerns regarding the risk of hypernatremia and dehydration in patients with renal dysfunction and electrolyte shifts that can lead to serious clinical consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that 1L PEG is not inferior to 2L PEG or other bowel preparations. [24][25][26] Xin Y et al reported that there were no significant differences in appropriate bowel preparation rates and complication rates in a meta-analysis of randomized, controlled trials with 1L PEG and 2L PEG. [27] Instead of improving compliance and taste, 1L PEG has raised concerns regarding the risk of hypernatremia and dehydration in patients with renal dysfunction and electrolyte shifts that can lead to serious clinical consequences.…”
Section: Discussionmentioning
confidence: 99%
“…This study will determine whether participants who are given bowel preparation instructions through a combination of dynamic multimedia (scheduled SMS, smartphone application, video instructions and email) have better adenoma detection and patient-reported measures compared with participants who are given standard written-based instructions. The study will use ultra-low volume 1 L polyethylene glycol with ascorbic acid (PEG-ASC) as the choice of bowel preparation given its superiority in achieving adequate bowel preparation versus other large volume PEG-based regimens, and possible high patient acceptability given its low volume 20 21. The study will also identify risk factors that predict poor bowel preparation, compare procedural and clinician time required between the two groups, identify colorectal cancer risk factors and explore the potential financial implications, including in pre-anaesthetic screening.…”
Section: Introductionmentioning
confidence: 99%